2016
DOI: 10.4012/dmj.2016-008
|View full text |Cite
|
Sign up to set email alerts
|

The marginal fit of E.max Press and E.max CAD lithium disilicate restorations: A critical review

Abstract: This critical review aimed to assess the vertical marginal gap that was present when E.max lithium disilicate-based restoration (Press and CAD) are fabricated in-vitro. Published articles reporting vertical marginal gap measurements of in-vitro restorations that had been fabricated from E.Max lithium disilicate were sought with an electronic search of MEDLINE (PubMed) and hand search of selected dental journals. The outcomes were reviewed qualitatively. The majority of studies that compared the marginal fit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 45 publications
2
61
0
5
Order By: Relevance
“…Marginal misfits of lithium disilicate ceramics have been reported to be minimal and within clinically acceptable limits . However, most studies have confirmed that heat‐pressed lithium disilicate restorations have better marginal fit the CAD/CAM restorations …”
Section: Subtractive Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…Marginal misfits of lithium disilicate ceramics have been reported to be minimal and within clinically acceptable limits . However, most studies have confirmed that heat‐pressed lithium disilicate restorations have better marginal fit the CAD/CAM restorations …”
Section: Subtractive Manufacturingmentioning
confidence: 99%
“…41 However, most studies have confirmed that heat-pressed lithium disilicate restorations have better marginal fit the CAD/CAM restorations. 42 Composition of CAD/CAM silicate ceramics, properties, and preparation requirement can be found in Table 4. 11,12,14,16,29,32 2.9 | Oxide ceramics enon is referred to as transformation toughening.…”
Section: Silicate Ceramicsmentioning
confidence: 99%
“…Recent improvements in the mechanical properties of lithium disilicate made it one of the most common materials for fabrication of indirect restoration in dental practice (1). Its excellent esthetics and mechanical properties (2) result in restorations with high survival rates (3).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the aim of the present study was to evaluate the effect of the combination of hydrofluoric acid or silane with the self-etching ceramic primer on the immediate and after 1-year of water storage on bonding efficacy, morphological etching pattern and chemical interaction of these bonding treatments to the lithium disilicate. The following null hypotheses were evaluated in the present study: [1] the combination of hydrofluoric acid or silane with the self-etching ceramic primer will not influence the bonding efficacy immediate and after 1-year of water storage; [2] the association of hydrofluoric acid with the self-etching ceramic primer does not improve the chemical interaction to lithium disilicate when compared to the use of a separate hydrofluoric acid or a separate self-etching ceramic primer and; [3] the association of hydrofluoric acid with the self-etching ceramic primer does not improve the morphological etching pattern to lithium disilicate compared to the use of a separate hydrofluoric acid or a separate self-etching ceramic primer.…”
Section: Introductionmentioning
confidence: 99%
“…The restoration geometry, design considerations, preparation methods, and loading conditions are key factors for the long-term success of dental restorations [2][3][4][5][6][7][8]. For tooth-colored ceramic inlays in esthetic dentistry, the long-term success is an actual problem [7].…”
Section: Introductionmentioning
confidence: 99%